Metal-organic frameworks and their derived materials for electrochemical energy storage and conversion: promises and challenges - Wu, Hao Bin (2018)
In addition to their conventional uses, metal-organic frameworks (MOFs) have recently emerged as an interesting class of functional materials and precursors of inorganic materials for electrochemical energy storage and conversion technologies. This class of MOF-related materials can be broadly categorized into two groups: pristine MOF-based materials and MOF-derived functional materials. Although the diversity in composition and structure leads to diverse and tunable functionalities of MOF-based materials, it appears that much more effort in this emerging field is devoted to synthesizing MOF-derived materials for electrochemical applications. This is in view of two main drawbacks of MOF-based materials: the low conductivity nature and the stability issue. On the contrary, MOF-derived synthesis strategies have substantial advantages in controlling the composition and structure of MOF-derived materials. From this perspective, we review some emerging applications of both groups of MOF-related materials as electrode materials for rechargeable batteries and electrochemical capacitors, efficient electrocatalysts, and even electrolytes for electrochemical devices. By highlighting the advantages and challenges of each class of materials for different applications, we hope to shed some light on the future development of this highly exciting area.